PERCEPTION OF CHOOSING CONVENTIONAL TAXI MODES AND ONLINE TAXIS AT PURABAYA TERMINAL - Firdausi, Mutiara; Huda, Muhammad Khusnul; Hafizah, Nafilah El (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2024)
Transport mode choice is a method for determining the choice of transportation mode for individuals on their way to a destination, which is influenced by several factors. This research focuses on the selection of transportation modes between conventional taxis and online taxis at the Purabaya Terminal in Sidoarjo. This study determined the characteristics of mode users, the factors influencing mode selection, the mode selection probability model, and the model sensitivity when a change occurred in each trip attribute. The data collection process was carried out by distributing questionnaires with the revealed preference technique to bus passengers who got off at Purabaya Sidoarjo Terminal. transport mode choice model data analysis used the binomial logit model and regression analysis. The results of multiple regression analysis to see the variables that influence the choice of mode found that the variables influencing the choice of mode in this study included gender, age, income, travel destination, estimated time, cost estimation, travel purpose, and mode background. The analysis using the binomial logit model revealed that at a waiting time of 5 minutes, the probability of choosing a conventional taxi was 1.40%, while the probability of choosing an online taxi was 98.64%. When the waiting time was 0 minutes, the probability of choosing a conventional taxi was 5.11%, while the probability of choosing an online taxi was 94.89%. In order for the chances of choosing a conventional taxi to be above 50%, the conventional taxi mode must reduce the waiting time by about 10 minutes so that a conventional taxi is chosen.